Dramaturgical Analysis of Viral TikTok Phenomena: Case Study of Janice Kaori's “Yareu” Video - Selfiani, Via; Imawan, Khaerudin (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze how Janice Kaori, as a content creator, presents herself on the TikTok platform, particularly in the “Yareu” content, by using the dramaturgical perspective proposed by Erving Goffman and examining its relation to the process of personal branding formation. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with audiences and observations of the TikTok content documentation uploaded by Janice Kaori. The findings indicate that Janice kaori consistently constructs a front stage through the use of the tagline “Yareu”, the use of a school uniform as a costume attribute, an expressive and energetic delivery style, and the selection of public spaces as recording locations. Meanwhile, on the back stage, there are visible processes of emotional management, preparation before content production, and efforts to maintain privacy boundaries in her personal life. This form of self-presentation demonstrates the management of public space (front stage) and private space (back stage) through the regulation of performance, the development of distinctive characteristics, and the establishment of boundaries between personal identity and the identity presented to the audience. The findings of this research suggest that consistency in self-presentation contributes to the formation of a strong, recognizable, and sustainable personal branding for non-celebrity content creators on the TikTok platform.